Learning experiences on YouTube, an analysis during the COVID-19 pandemic - Vera Balderas, Seira; Moreno Tapia, Javier (IE Revista de Investigación Educativa de la REDIECH, 2021)
The migration from face-to-face education to a virtual one due to the health contingency that is experienced in the world due to the coronavirus brought great challenges, to face them, information and communication technologies (ICT) represent a key element for students who use the spaces they have generated to learn beyond the classroom. The objective of this article is to analyze the uses that students of a public university in Mexico make of YouTube during the pandemic that occurred in 2020 due to COVID-19, and to identify the educational uses that they give to the tool in formal and non-formal learning spaces. The study approach was quantitative and a questionnaire developed in Google Forms was used as an instrument for data collection, which was applied to 149 students. The results showed that the participants frequently use YouTube to acquire knowledge related to different areas of their life, recovering valuable learning. It is concluded that students recognize YouTube as an alternative learning space, which can be implemented as a resource in the teaching and learning processes in formal education.